HUMOR AS THE COUNTERCAST OF COMEDY AND TACTFULNESS - Evan Wardiannata; Dhea Amanda, Rendy Pernando, Gea Octavilla, Leonardo Siburian, Marselina (ADISAM PUBLISHER, 2023)
This research aims to examine the extent to which humor is able to serve as a crossing space for comedy, whether it is comedy with a little allusion to the ancient Greek school or humor over the expectations of someone or a group deemed excessive or even as a tool for resistance that is often used, for example in Indonesia in formal or informal events (YouTube). This research is literature research by searching and analyzing data through secondary sources or journals that are compatible with the topic of discussion. The results show that humor, comics, life drama, fatigue, encountering ideas wrapped in cuteness, taste, becomes meaningful when it is in a space of surprise, beyond expectations but able to refresh laughter as well as disarming the rigidity of the self